Expert Consensus Recommendations for the Suspicion and Diagnosis of Transthyretin Cardiac Amyloidosis. (September 2019) - Maurer, Mathew S.; Bokhari, Sabahat; Damy, Thibaud; Dorbala, Sharmila; Drachman, Brian M.; Fontana, Marianna; Grogan, Martha; Kristen, Arnt V.; Lousada, Isabelle; Nativi-Nicolau, Jose; Cristina Quarta, Candida; Rapezzi, Claudio; et al.
Abstract : Cardiomyopathy is a manifestation of transthyretin amyloidosis (ATTR), which is an underrecognized systemic disease whereby the transthyretin protein misfolds to form fibrils that deposit in various tissues and organs. ATTR amyloidosis is debilitating and associated with poor life expectancy, especially in those with cardiac dysfunction, but a variety of treatment options have recently become available. Considered a rare disease, ATTR amyloidosis may be more prevalent than thought, particularly in older persons. Diagnosis is often delayed because of a lack of disease awareness and the heterogeneity of symptoms at presentation. Given the recent availability of effective treatments, early recognition and diagnosis are especially critical because treatment is likely more effective earlier in the disease course. The Amyloidosis Research Consortium recently convened a group of experts in ATTR amyloidosis who, through an iterative process, agreed on best practices for suspicion, diagnosis, and characterization of disease. This review describes these consensus recommendations for ATTR associated with cardiomyopathy as a resource to aid cardiologists and others in the recognition and diagnosis of ATTR associated with cardiomyopathy. Included in this review is an overview of red flag signs and symptoms and a recommended diagnostic approach, including testing for monoclonal protein, scintigraphy, or biopsy and, if ATTR associated with cardiomyopathy is identified, TTR genotyping.